Akuntansi Zakat PSAK 109 dalam Penguatan Good Corporate Lembaga Amil Zakat di Kabupaten Pamekasan - Sri Handayani (Institut Agama Islam Negeri Madura, 2019)
One of the three pillars for Muslims is the obligation to pay zakat according to provisions. Zakat is intended for people who are deficient. In Indonesia, poverty is still visible in some communities, this is what shows the role of zakat can contribute in breaking down poverty. Good and transparent management is an accountable financial responsibility. Indonesia has an accounting recording standard in the form of PSAK number 109 concerning zakat accounting. The purpose of this study is to analyze the accounting treatment of zakat PSAK 109 in strengthening good corporate governance of the Amil Zakat Institution. The results of his research show that the accountability report of the amil zakat party in the form of financial reports has been made, the accounting records of the institution understand the incoming and outgoing funds, the conversion of non-cash funds at market prices, incoming halal and non-halal funds and have followed the Law Republic of Indonesia Number 23 of 2011 concerning Management of Zakat although there are some things that are still not well understood.[salah satu rukun ketiga bagi umat islam adalah kewajiban membayar zakat sesuai ketentuan. Zakat diperuntukan bagi masyarakat yang kekurangan. Di Indonesia masih terlihat kemiskinan di beberapa masyarakat, hal inilah yang menunjukkan peran zakat dapat ikut andil dalam mengurai kemiskinan tersebut. Pengelolaan yang baik dan transparan merupakan pertanggungjawaban keuangan yang akuntabel. Indonesia mempunyai standar pencatatan akuntansi berupa PSAK nomer 109 tentang akuntansi zakat Adapun tujuan penelitian ini adalah menganalisis perlakuan akuntansi zakat PSAK 109 dalam penguatan good corporate Lembaga Amil Zakat. Hasil penelitiannya menunjukkan bahwa laporan pertanggungjawaban pihak amil zakat berupa laporan keuangan sudah di buat, pencatatan akuntansi pihak lembaga sudah paham mengenai dana masuk dan dana keluar , konversi dana non tunai dengan harga pasar, yang masuk dana halal dan non halal serta telah mengikuti Undang-Undang Republik Indonesia Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat meskipun ada beberapa hal yang masih belum dipahami dengan baik.]